أثر الرقابة الإدارية على أداء الأفراد العاملين دراسة حالة مديرية الصيانة سونطراك بالأغواط - حلموس عمر; مكانزية إبراهيم الخليل; صفراني عائشة (جامعة عمار ثليجي الاغواط, 2022)
This study aimed to know the extent of the impact of administrative control on the performance of individuals working in Sonatrach Maintenance Directorate - Laghouat- To achieve this process, we distributed a questionnaire to a random sample consisting of (50) factors, so that (45) questionnaires were retrieved, from which (5) were excluded, which were not valid for the study. (40) questionnaires were processed using a set of statistical methods using the statistical program SPSS to analyze its data, which are represented in (arithmetic averages, standard deviations, coefficients of variation ...) as the results of the study showed a significant effect of administrative control on the performance of workers embodied in two dimensions (control comprehensive) and (control at the individual level). in addition to the presence of significant differences in the trends of the individual sample in the institution under study due to the variable (age and years of service). Finally, the study recommended the necessity of paying attention to the application of administrative control to improve the performance of employees, imposing a strict control system at the same time characterized by flexibility, and spreading a culture of respect for internal laws through the practice of individuals to apply control procedures where deviations are addressed through the exchange of opinions, to achieve the desired goals of the organization.